2011
DOI: 10.1111/j.1582-4934.2011.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Nox2 and Nox4 mediate tumour necrosis factor-α-induced ventricular remodelling in mice

Abstract: Reactive oxygen species (ROS) and pro-inflammatory cytokines are crucial in ventricular remodelling, such as inflammation-associated myocarditis. We previously reported that tumour necrosis factor-α (TNF-α)-induced ROS in human aortic smooth muscle cells is mediated by NADPH oxidase subunit Nox4. In this study, we investigated whether TNF-α-induced ventricular remodelling was mediated by Nox2 and/or Nox4. An intravenous injection of murine TNF-α was administered to a group of mice and saline injection was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Similar studies have reported the effective use of siRNAs to knockdown both Nox and Mfn2 and inhibit ROS production and apoptosis in cardiac cells, including HL‐1 cardiomyocytes (Yeh et al, 2011), H9c2 cardiomyocytes, (Shen et al, 2007), cultured neonatal rat cardiomyocytes (Papanicolaou et al, 2011) and mouse ventricular cells (Moe et al, 2011). However, while this investigation found no changes in apoptosis in DOX‐treated HL‐1 cardiomyocytes in the presence of Nox2 or Mfn2 knockdown, it is possible that efficacy of transfection may have influenced the measured endpoint.…”
Section: Discussionmentioning
confidence: 72%
“…Similar studies have reported the effective use of siRNAs to knockdown both Nox and Mfn2 and inhibit ROS production and apoptosis in cardiac cells, including HL‐1 cardiomyocytes (Yeh et al, 2011), H9c2 cardiomyocytes, (Shen et al, 2007), cultured neonatal rat cardiomyocytes (Papanicolaou et al, 2011) and mouse ventricular cells (Moe et al, 2011). However, while this investigation found no changes in apoptosis in DOX‐treated HL‐1 cardiomyocytes in the presence of Nox2 or Mfn2 knockdown, it is possible that efficacy of transfection may have influenced the measured endpoint.…”
Section: Discussionmentioning
confidence: 72%
“…TNF-␣ has been described to be an important mediator of atherogenesis (42), as well as to regulate Nox expression in cell culture (43) and mouse models (44). Therefore we expected that genetic inactivation of the Tnf-␣ gene in TTP Ϫ/Ϫ mice normalizes the atherogenic phenotype.…”
Section: Inactivation Of the Tnf-␣ Gene In Ttpmentioning
confidence: 99%
“…The dose of TNF-α injection was chosen from previous studies in mice that have reliably induced systemic and hepatic inflammation 13, 14 and from our pilot studies (described later) to avoid any significant detrimental effects on left ventricular (LV) function. After 16 weeks, animals were killed by being placed in a box connected to a CO2 gas cylinder in which the inflow of gas could be precisely regulated.…”
Section: Study Protocolmentioning
confidence: 99%
“…We had previously demonstrated that a single bolus injection of 8 μg/kg TNF-α in mice resulted in an increase in LV size and a decrease in systolic function after 28 days. 14 We therefore used 2 lower doses of TNF-α (2 and 4 μg/kg) in 18 mice (6 for each dose and 6 controls, which received saline injection). Echocardiographic measurements of LV size and function and LA diameter were assessed at baseline and after 4 weeks.…”
Section: Determination Of Optimal Tnf-α Dosementioning
confidence: 99%